Buckling behaviors of aluminum foam-filled aluminum alloy composite columns under axial compression. (August 2022) - Cui, Guangming; Meng, Lingzhao; Zhai, Ximei
Abstract: In this study, a new 6082-T6 aluminum alloy composite column filled with aluminum foam was proposed. Thirteen axial compression tests were performed on the aluminum foam-filled 6082-T6 aluminum alloy specimens with various slenderness ratios and diameter–thickness ratios. The load–lateral displacement relationships, surface strain histories, failure modes, and buckling characteristics of the composite specimens were obtained. Finite element (FE) models of the aluminum foam-filled aluminum alloy columns under axial compression were established using the non-linear finite element analysis (FEA) software ABAQUS/Standard. After verifying the accuracy of the FE model, the influence of the aluminum foam on the stability and buckling bearing capacity of the columns was discussed, and the effect of the combination of the external aluminum column and aluminum foam filling was analyzed based on the numerical results. Parametric studies were also conducted to reveal the influences of the geometric parameters (including the slenderness ratio, diameterto-to-thickness ratio, and cross-section) and material properties (including aluminum alloy with different grades and aluminum foam with various densities) on the buckling behavior and buckling bearing capacity of the composite columns. In addition, the failure mechanism of this new type of composite column, considering the supporting effect of the aluminum foam on the foam-filled aluminum columns with thin walls, was investigated. Highlights: A novel aluminum-foam filled 6082-T6 aluminum alloy composite columns is proposed. The composite column exhibits better deformation performance than the empty column. The influence of geometric parameters and material properties are investigated. The aluminum-foam and empty column work together to restrain the local buckling.